CAMP‐Induced Nuclear Condensation of CRTC2 Promotes Transcription Elongation and Cystogenesis in Autosomal Dominant Polycystic Kidney Disease (Adv. Sci. 10/2022). Issue 10 (5th April 2022) - Mi, Zeyun; Song, Yandong; Wang, Jiuchen; Liu, Zhiheng; Cao, Xinyi; Dang, Lin; Lu, Yumei; Sun, Yongzhan; Xiong, Hui; Zhang, Lirong; Chen, Yupeng
Abstract : cAMP‐Induced Nuclear Condensation of CRTC2 Biomolecular condensates play key roles in controlling gene expression in response to internal and external signals. In article number 2104578, Yupeng Chen and co‐workers elucidate a mechanism by which CREB‐regulated transcription coactivator 2 (CRTC2) nuclear condensation conveys cAMP signaling to promote transcription elongation and cystogenesis in autosomal dominant polycystic kidney disease (ADPKD). The cover illustrates that upon activation of cAMP (represented as turning on the switch), CRTC2 translocates to the nucleus and forms phase‐separated condensates (represented as orange oil droplets that accrete through the gear transmission), thereby activating cyst‐associated gene expression to promote cyst growth (represented as gears that become larger and sharper).